Global finance and the macroeconomy - Makin, A. J. (Houndmills, England ; New York : Palgrave Macmillan, 2003)
This book provides new ways of analyzing the key issues in international finance and open economy macroeconomics. The topics covered include: financial globalization and the evolution of the international financial system; international macroeconomic accounting and measurement; early balance of payments approaches; the inter-temporal model of international borrowing and lending; the significance of external deficits; the determinants of interest rate differentials and exchange rates; the effectiveness of monetary and fiscal policies; capital mobility and economic growth; and the causes of financial crisis in emerging economies.
Includes bibliographical references (p. 185-194) and index.
rpm 25/08/16
Loans
Keywords: International finance; Macroeconomics